2011
DOI: 10.1111/j.1439-0264.2011.01064.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the Non-Sensory Tissue Components in Rat Aging Vomeronasal Organ

Abstract: The vomeronasal organ (VNO) is a chemosensory organ that detects environmental pheromones. The morphology of the 'non-sensory' epithelium (NSE) of the VNO and its lamina propria, as well as how it relates to ageing has received little attention. Histological, histochemical, morphometric and ultrastructural techniques were used to study the morphological structure of the rat NSE in five adult (3 months old) and five aged (2-2.5 years old) male albino rats. In adult rats, the NSE contained dark and light columna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The frequent detection of neutrophils invading rabbit NSE is likely, Getchell and Kulkarni () found infiltration of the NSE among mammals that possessed a VNO surrounded by a bony capsule. Infiltrating cells into the VNO–NSE have also been observed in rats (Breipohl et al., ; Eltony and Elgayar, ), slow loris (Loo and Kanaqasunteram, ), dogs (Adams and Wiekamp, ), virus antibody‐free rats (Getchell and Kulkarni, ) and tree shrews and Getchell and Kulkarni () suggested that neutrophils provide immune surveillance for the presence of pathogens in the material drawn from the nasal cavity into the VNO and can act as a first line of defence in preventing the invasion of the VNO parenchyma. The transient focal ischaemia, during VN pump action, followed by reperfusion and release of neutrophils chemoattractants was the mechanism suggested being responsible for neutrophils intra‐epithelial infiltration (Getchell and Kulkarni, ).…”
Section: Discussionmentioning
confidence: 91%
“…The frequent detection of neutrophils invading rabbit NSE is likely, Getchell and Kulkarni () found infiltration of the NSE among mammals that possessed a VNO surrounded by a bony capsule. Infiltrating cells into the VNO–NSE have also been observed in rats (Breipohl et al., ; Eltony and Elgayar, ), slow loris (Loo and Kanaqasunteram, ), dogs (Adams and Wiekamp, ), virus antibody‐free rats (Getchell and Kulkarni, ) and tree shrews and Getchell and Kulkarni () suggested that neutrophils provide immune surveillance for the presence of pathogens in the material drawn from the nasal cavity into the VNO and can act as a first line of defence in preventing the invasion of the VNO parenchyma. The transient focal ischaemia, during VN pump action, followed by reperfusion and release of neutrophils chemoattractants was the mechanism suggested being responsible for neutrophils intra‐epithelial infiltration (Getchell and Kulkarni, ).…”
Section: Discussionmentioning
confidence: 91%
“…However, in guinea pig we distinguished four types of cells with different characteristic morphological features. Detection of dark and light cells have been reported frequently in many tissues as developing hamster HG (Lopez et al, 1992) and adult rat (Eltony and Elgayar, 2011) and developing rabbit (Elgayar et al, 2014) vomeronasal organ. Presence of more than one cell type in many HGs has often been interpreted as being one cell type in different activity levels (Payne, 1994;Lopez et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have focused on the NSE of the VNO. This epithelium has been described both as stratified and as pseudostratified, depending on the animal species analyzed (Eltony & Elgayar, 2011; Garrosa et al, 1998).…”
Section: Introductionmentioning
confidence: 99%